Effect of delayed diagnosis and treatment of congenital hypothyroidism on intelligence and quality of life: an observational study (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Congenital hypothyroidism is one of the most prevalent, albeit preventable causes of intellectual disability. This study determined the intellectual outcome and health-related quality of life (QoL) in children and adolescents clinically diagnosed with congenital hypothyroidism and the associations among age of starting thyroid hormone treatment, current free thyroxine (FT4) level, intelligence quotient (IQ), and QoL.METHODS Intelligence (Wechsler scales) and QoL (PedsQLTM 4.0 parent proxy-report) tests were administered to 25 patients with congenital hypothyroidism in the pediatric clinic of Cipto Mangunkusumo Hospital, Jakarta. Nineteen patients underwent thyroid ultrasonography or scintigraphy to determine the etiology of congenital hypothyroidism.RESULTS A total of 25 patients with the median age of 9 (5.5–12.5) years were recruited. Eighteen patients had a total IQ of <70. The age of treatment initiation did not correlate with full scale IQ (FSIQ) (r = −0.261, p = 0.071) and verbal IQ (VIQ) (r = −0.232, p = 0.265). The late initiation of treatment was correlated with lower performance IQ (PIQ) (r = −0.325, p = 0.025). The higher current FT4 levels was correlated with higher scores ofFSIQ (r = 0.314, p = 0.046) and PIQ (r = 0.320, p = 0.043). The late initiation of treatment (r = 0.006, p = 0.980) and higher current FT4 levels (r = 0.246, p = 0.310) were not correlated with QoL. Hemiagenesis of thyroid gland was the most common etiology.CONCLUSIONS The late initiation of thyroid hormone substitution in patients with congenital hypothyroidism negatively affects intellectual abilities.